THE ROLE OF RELIGIOUS MODERATION ON LIFE SATISFACTION OF GENERATION Z MUSLIMS - Zulmi Ramdani; Yonathan Natanel; Busro Busro (Balai Penelitian dan Pengembangan Agama Jakarta, 2022)
Religious moderation is considered one of the crucial issues discussed by many parties. This circumstance is evidenced by varied rules and facts, making it an indicator of the nation's welfare. The lack of research that specifically addressed the correlation between religious moderation and psychological attributes was one reason why this study was conducted. Hence, the purpose of the present research was to determine the role of religious moderation on the life satisfaction of generation Z Muslim students. A quantitative design engaging a causal approach was employed to measure the significance of the role of religious moderation on the life satisfaction of generation Z Muslims. 453 respondents selected using the purposive sampling technique participated in this study. To collect the data, researchers administered two tested measuring instruments that indicated good psychometric properties. The regression analysis results revealed a significant impact of religious moderation on the life satisfaction of generation Z Muslim students. Meanwhile, the categorization of respondents confirmed that most of them had moderate and high levels of understanding of religious moderation. This study concluded that to achieve high life satisfaction, religious moderation could be considered an essential aspect of social life. Correspondingly, the findings could be implied as a reference for policymakers at Islamic educational institutions in forming an awareness of the importance of religious moderation among generation Z Muslims studying at Islamic universities in Indonesia.